2018
DOI: 10.1039/c8tb02493f
|View full text |Cite
|
Sign up to set email alerts
|

Dual antibacterial behavior of a curcumin–upconversion photodynamic nanosystem for efficient eradication of drug-resistant bacteria in a deep joint infection

Abstract: The curcumin–upconversion photodynamic nanosystem exhibits dual antibacterial behavior for MRSA-induced periprosthetic joint infection under NIR irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Several kinds of UCNPs were applied to covert NIR to visible light or UV light for triggering PDT in tumor therapy or antibacterial application [29,30,31]. Gulzar et al synthesized a nanocomposite based on nanographene oxide-UCNPs-Ce6 as a theranostic platform for the upconversion luminescence imaging-guided PDT/PTT of cancer [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several kinds of UCNPs were applied to covert NIR to visible light or UV light for triggering PDT in tumor therapy or antibacterial application [29,30,31]. Gulzar et al synthesized a nanocomposite based on nanographene oxide-UCNPs-Ce6 as a theranostic platform for the upconversion luminescence imaging-guided PDT/PTT of cancer [29].…”
Section: Resultsmentioning
confidence: 99%
“…Such a near-infrared (NIR) triggered UCNPs-CPZ-PVP system significantly reduced the aggregation of CPZ and presented a high anti-infectious activity against multi-drug resistant bacteria (methicillin-resistant Staphylococcus aureus by 4.7 log and multi-drug resistant Escherichia coli by 2.1 log). Another study investigated the dual antibacterial behavior induced by the curcumin-UCNPs itself and induced by photodynamic therapy were demonstrated [31]. The results showed that nearly 100% methicillin-resistant Staphylococcus aureus was eradicated using curcumin-UCNPs under the NIR irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, besides coating on the surface of bone implants, the NIR light-responsive nanomaterials could also be injected into the knee joint for the clinical treatment of periprosthetic joint infection. Liu et al 93 has reported curcumin‑upconversion nanoparticles (curcumin-UCNPs) for the efficient eradication of drug-resistant bacteria in a deep joint infection by producing singlet oxygen under NIR light irradiation. Curcumin is an extract from the plant Curcuma longa , which has intrinsic antibacterial and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…And the dispersion and antimicrobial of UNCP‐PSs can be improved with selected coating materials. Combining with the emitting light of UNCPs, in vivo therapeutic exercise can be designed with imaging tracking function, especially in the treatment of inflammation [83, 84] and cancer [54, 85] in deep tissues. Multifunctional UNCP‐PS with multi‐layer core–shell structure is a hot research topic, such as a composite nanoparticle with all magnetic resonance (MRI) imaging, upconversion luminescence (UCL) imaging, photodynamic/sonodynamic antibacterial and quaternised surface layer [56].…”
Section: Discussionmentioning
confidence: 99%